Shopping centres in decline: analysis of demalling in Lisbon - Guimarães, Pedro (2019)
Cities and retail are intrinsically connected and in evolution. Malling in the United States is characterised by the peripheral implementation of large shopping centres in close connection with urban sprawl that characterise the urban development of that country. However, in a process that has been gaining relevance, several shopping centres have declined. A practice commonly referred to as demalling emerged, through which shopping centres began to be redeveloped to acquire new functions. Although more incipient, in Europe this process is just now evolving as some shopping centres begin to decline becoming dead malls. The aim of this article is to explore demalling, unfolding evidences of such practice in this latter geographical context. Based on a case study methodology, we developed fieldwork in Lisbon municipality and analysed 55 shopping centres. Our main results stress the low economic viability of the majority of these retail precincts and uncovered that several redevelopment measures are already in place, framing the demalling process of that city. Overall, two main categories of interventions were unfolded, both of which possess similarities to the measures implemented in North America: (i) moving out, in which the shopping centre appropriates part of the public space; (ii) functional requalification, in which other functions become relevant to the detriment of the previous exclusive commercial function.